Privacy and Security in the Digital Age - Michael Friedewald (Routledge, 2014)
Privacy and data protection are recognized as fundamental human rights. Recent developments, however, indicate that security issues are used to undermine these fundamental rights. As new technologies effectively facilitate collection, storage, processing and combination of personal data government agencies take advantage for their own purposes. Increasingly, and for other reasons, the business sector threatens the privacy of citizens as well.